Diterminan Kejadian Malaria Di Kawasan Kerja Puskesmas Luas Kabupaten Kaur Provinsi Bengkulu - Jipri Suyanto; Puja Lestari; Retni Retni (Malahayati Nursing Journal, 2025)
ABSTRACT An inciting factor, frequently overlooked by the community itself, leads to a rise in instances. Hence, it is imperative to conduct a study to identify the triggers or elements that might facilitate the discovery of remedies to mitigate or decrease instances within a community. To determine the factors that contribute to the occurrence of malaria in the service area of Luas Public Health Centre, located in Kaur Regency, Bengkulu Province. During a one-month research period, researchers employed the purposive sampling technique to carefully pick samples. The study was done at the Luas Public Health Centre, located in the Kaur District. Our data analysis involves the utilization of both the univariate test and the chi-square test. The analysis shows that around 35 respondents, which is a substantial proportion, reported experiencing malaria. More than half of the respondents, specifically 39, had poor knowledge. Additionally, almost half of the respondents, 35 in total, lived less than 1 kilometer away from livestock, while almost half, 30 respondents, lived less than 75 meters away from a plantation. The chi square test revealed a significant association between knowledge (p-value: 0.004), house distance to livestock jams (p-value: 0.001), and house distance to plantations (p-value: 0.019) with the incidence of malaria cases in the service area of Luas Public Health Center in Kaur District, Bengkulu Province. Fostering partnerships with health services and implementing the principles of hygiene and wellness are crucial factors in enhancing the overall health condition within the community. Hence, it is imperative for individuals and communities to endorse government initiatives aimed at diminishing the prevalence of malaria through the implementation of physical activity, hygienic practices, and the elimination of mosquito breeding grounds. Engage actively in the health initiative by spreading positive information and promoting healthy habits among their families and communities. Keywords: Malaria Prevalence, Awareness, Proximity of House to Cow Shed, Proximity of House to Plantation.  ABSTRAK Peningkatan suatu kasus disebabkan oleh suatu komponen pemicu yang sering kali tidak disadari oleh Masyarakat itu sendiri. Oleh karena itu, perluhnya suatu kajian untuk mencari diterminan atau faktor tersebut yang dapat membantu dalam pencari solusi untuk penekanan atau penuruan kasus di suatu komunitas. Untuk Mengetahui determinan kejadian malaria di Kawasan kerja Puskesmas Luas Kabupaten Kaur Provinsi Bengkulu. Penelitian ini menggunakan desain cross sectional yang dilaksanakan di Kawasan Puskesmas Luas Kabupaten Kaur Provinsi Bengkulu dengan jumlah respoden sebanyak 72 responden. Teknik dalam menseleksi sampel menggunaka teknik purposive sampling dengan lama penelitian selama 1 bulan. Sedangkan analisis data menggunakan uji univariat dan uji chi square. Dari hasil analysis diketahui bahwa hampir Sebagian besar dari responden mengalami malaria sebanyak 35 responden, lebih dari setengah dari responden memiliki pengetahuan kurang baik sebanyak 39 responden, hampir sebagian dari responden memiliki jarak rumah dengan kadang ternak 1 KM sebanyak 35 responden, dan hampir sebagian dari responden memiliki jarak rumah dengan Perkebunan ≤75 M sebanyak 30 responden. Sedangkan hasil uji chi square menemukan bahwa adanya hubungan pengetahuan (p-value: 0.004), jarak rumah dengan kendang ternak (p-value: 0.001), dan jarak rumah dengan Perkebunan (p-value: 0,019) dengan kejadian malaria di Kawasan kerja Puskesmas Luas Kabupaten Kaur Provinsi Bengkulu. Kolaborasi dengan pihak pelayanan kesehatan dan menerapkan konsep hidup bersih dan sehat merupakan salah satu kunci dalam peningkatan derajat kesehatan di masyarakat itu sendiri. Oleh karena itu, hendaknya responden/masyarakat memberikan dukungan akan program pemerintah dalam menekan angka kejadian dari malaria itu sendiri dengan menerapkan olahraga, PHBS dan pemberantasan sarang nyamuk. Juga ikut andil dalam program kesehatan itu sendiri seperti, saling memberikan informasi yang positif dan menjaga pola atau lifestyle di keluarga mereka dan lingkungan mereka sendiri. Kata Kunci: Kejadian Malaria, Pengetahuan, Jarak Rumah Dengan Kandang Ternak, Jarak Rumah Dengan Perkebunan.